2017
DOI: 10.22159/ijpps.2017v9i12.21220
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Eosin Dye as an Ion Pairing Agent for Determination of Pharmaceuticals: A Brief Review

Abstract: Globally, dyes are widely used in the pharmaceutical, food, textile, cosmetics, plastics, leather, paint, ink and paper industries. Eosin is an acidic orange-pink dye and has very strong staining properties. Haematoxylin and eosin Y (H and E) combination is the most common staining and primary diagnostic technique in histo-pathological laboratories. This review mainly discussed the utility of eosin dye in quality control laboratories as an ion pairing agent for drug analysis. Eosin Y is one the most common ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…In conclusion, Eosin Y, the most commonly used xanthan dye in histological and drug analysis studies (Rahman, 2017), showed inhibition effect on hCA I and hCA II isoenzymes. Carbonic anhydrase inhibitors are drug candidates for the treatment of many diseases, from glaucoma to neuropathic pain (Supuran, 2018).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In conclusion, Eosin Y, the most commonly used xanthan dye in histological and drug analysis studies (Rahman, 2017), showed inhibition effect on hCA I and hCA II isoenzymes. Carbonic anhydrase inhibitors are drug candidates for the treatment of many diseases, from glaucoma to neuropathic pain (Supuran, 2018).…”
Section: Discussionmentioning
confidence: 75%
“…In addition, Eosin Y is also one of the most common ion-coupling agents, and its mono and di-anionic forms can interact with many drug molecules. Therefore, it belongs to the xanthan dye group, which is widely used in the analysis of many drugs (Waheed et al, 2000;Rahman, 2017). In this study, in order to investigate the inhibitory effects of eosin Y on hCA I and hCA II isoenzymes, firstly, CA I and CA II isoenzymes were purified from human erythrocytes and the purification table was prepared with the data obtained (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ternary complex formation has been considered to be of an important role in the field of spectrophotometric analysis [13,14]; they are divided into two types, ion-association and a mixed-ligand complex. Different pharmaceutical compounds have been analyzed using ion-pair complexes [15,16]. Meanwhile, the formation of ternary complexes starts to get much attention [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…They belong to the group of xanthene fluorescent dyes with a wide range of photophysical and biological applications, due to their low toxicity in vivo, and high water solubility [3]. The utility of eosin derivatives is associated to their good spectral characteristics and the possibility to interact with different type of biomolecules [4][5][6][7][8]. Photophysical properties of eosin in solution strongly depend on the solvents polarity and possibility of hydrogen bond formations.…”
Section: Introductionmentioning
confidence: 99%